A two-compartment bone tumor model to investigate interactions between healthy and tumor cells. (5th March 2020) - Komez, Aylin; Buyuksungur, Arda; Antmen, Ezgi; Swieszkowski, Wojciech; Hasirci, Nesrin; Hasirci, Vasif
Abstract: We produced a novel three-dimensional (3D) bone tumor model (BTM) to study the interactions between healthy and tumor cells in a tumor microenvironment, the migration tendency of the tumor cells, and the efficacy of an anticancer drug, Doxorubicin, on the cancer cells. The model consisted of two compartments: (a) a healthy bone tissue mimic, made of poly(lactic acid-co-glycolic acid) (PLGA)/beta-tricalcium phosphate ( β -TCP) sponge seeded with human fetal osteoblastic cells (hFOB) and human umbilical vein endothelial cells (HUVECs), and (b) a tumor mimic, made of lyophilized collagen sponge seeded with human osteosarcoma cells (Saos-2). The tumor mimic component was placed into a central cavity created in the healthy bone mimic and together they constituted the complete 3D bone tumor model (3D-BTM). The porosities of both sponges were higher than 85% and the diameters of the pores were 199 ± 52 μ m for the PLGA/TCP and 50–150 μ m for the collagen scaffolds. The compression Young's modulus of the PLGA/TCP and the collagen sponges were determined to be 4.76 MPa and 140 kPa, respectively. Cell proliferation, morphology, calcium phosphate forming capacity and alkaline phosphatase production were studied separately on both the healthy and tumor mimics. All cells demonstrated cellular extensions and spread well in porous scaffolds indicating good cell–material interactions. Confocal microscopy analysis showed direct contact between the cells present in different parts of the 3D-BTM. Migration of HUVECs from the healthy bone mimic to the tumor compartment was confirmed by the increase in the levels of angiogenic factors vascular endothelial growth factor, basic fibroblast growth factor, and interleukin 8 in the tumor component. Doxorubicin (2.7 μ g.ml −1 ) administered to the 3D-BTM caused a seven-fold decrease in the cell number after 24 h of interaction with the anticancer drug. Caspase-3 enzyme activity assay results demonstrated apoptosis of the osteosarcoma cells. This novel 3D-BTM has a high potential for use in studying the metastatic capabilities of cancer cells, and in determining the effective drug types and combinations for personalized treatments.